2016 IEEE 28th International Conference on Tools With Artificial Intelligence (ICTAI) 2016
DOI: 10.1109/ictai.2016.0078
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Apple Tree Disorders Using Convolutional Neural Networks

Abstract: This paper studies the use of Convolutional Neural Networks to automatically detect and classify diseases, nutritional deficiencies and damage by herbicides on apple trees from images of their leaves. This task is fundamental to guarantee a high quality of the resulting yields and is currently largely performed by experts in the field, which can severely limit scale and add to costs. By using a novel data set containing labeled examples consisting of 2539 images from 6 known disorders, we show that trained Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 6 publications
(6 reference statements)
1
42
0
5
Order By: Relevance
“…Moreover, Nachtigall et al [18] made use of CNNs to detect and classify nutritional deficiencies and damage on apple trees. AlexNet was used as CNN architecture, so they made a comparison between Multilayer Perceptron (MLP) and the CNN, which was compared with seven volunteer experts.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, Nachtigall et al [18] made use of CNNs to detect and classify nutritional deficiencies and damage on apple trees. AlexNet was used as CNN architecture, so they made a comparison between Multilayer Perceptron (MLP) and the CNN, which was compared with seven volunteer experts.…”
Section: Related Workmentioning
confidence: 99%
“…The simulation result has shown that 90% of appropriate identification rate is achieved on apple disease leaf illustration and has shown that the proposed work model is efficient and feasible. Lucas G. Nachtigall et al [2] have studied the usage of CNN for automatically classifying and detecting the diseases, nutritional deficiencies and is being damaged by the apple trees herbicides from the leave images. This fundamental task is to ensure the enhanced quality of yields and is more executed by the scholars in the field that could lessen the scale and add the cost.…”
Section: Related Workmentioning
confidence: 99%
“…The general diseases are in the form of spots, which are yellow and brown. The other diseases are in the form of fungus, bacterial diseases, and virus [2]. Bin Liu et al identified the plant leaf disease by determining the illness of a plant.…”
Section: Introductionmentioning
confidence: 99%
“…Soft computing approaches have become the de facto approach for agricultural robotics as they have been found to be able to handle dynamic conditions reliably (Y. Huang et al, ). They have been utilised for a wide range of agricultural tasks: harvesting, yield estimation, weed‐spraying, pollination, and crop management (Bargoti & Underwood, a, b; Dias, Tabb, & Medeiros, ; Kurosaki et al, ; Nachtigall, Araujo, & Nachtigall, ; Sa et al, ; Wan, Toudeshki, Tan, & Ehsani, ; Wang, Song, & He, ; Zhang et al, ). Detection of apples (Bargoti & Underwood, b; Dias et al, ; Inthiyaz, Kishore, & Madhav, ; Moallem, Serajoddin, & Pourghassem, ; Prasad et al, ; Puttemans, Vanbrabant, Tits, & Goedemé, ; Soleimani Pour, Chegini, Zarafshan, & Massah, ) and strawberries (Habaragamuwa et al, ; Puttemans et al, ) has shown good results with detection rates up to 90% of the fruit under real‐world orchard conditions.…”
Section: Related Workmentioning
confidence: 99%